Life Satisfaction, Problematic Social Media Use and Self-Esteem as the Mediator (Jurnal Bimbingan Konseling, 2020)
This study attempted to identify and analyze the relationship between life satisfaction, and problematic social media use on students by using self-esteem as the mediator. To do so, the population involved in this study were students of Public Junior High School (SMP Negeri) throughout Semarang City who used social media with the sample of 345 students selected using cluster random sampling technique. For more, their data were collected using the life satisfaction scale, Bergen Social Media Addiction Scale (BSMAS), and self-esteem inventory (SEI). The results of mediation analysis indicated that the indirect effect of life satisfaction and problematic social media use mediated by self-esteem was significant, while the direct effect was not significant. Thus, this study contributes implications for counselors in providing classical guidance service with a discussion related to the use of social media with the aim of preventing problematic social media use.